Endothelial CaSR is involved in the induction of atherosclerosis by promoting cell adhesion and local inflammation. (10th June 2022) - Sundararaman, S; Peters, L; Bonnin Marquez, A; Bouma, J; Maas, S; Jansen, Y; Gencer, S; Soehnlein, O; Wagner, U; Bidzhekov, K; Weber, C; Doering, Y; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Humboldt foundation Background: Calcium-Sensing Receptor (CaSR) is a cell surface G-protein coupled receptor that senses calcium in the extracellular environment. This receptor is widely studied in mineral homeostasis due to its presence in varied calcitropic tissues. However, CaSR is also present on the surface of vascular and hematopoietic cells and recent studies suggest that this receptor can also have pathological consequences related to cardiovascular diseases, like atherosclerosis. Since endothelial cells are crucial players in atherogenesis, we aimed to investigate which role endothelial CaSR plays in the development and progression of atherosclerosis. Methods: We cross-bred CaSRflox/flox Apoe-/- mice with BmxCreERT2 Apoe-/- (endothelial cell specific Cre driver) mice to obtain tamoxifen-inducible mice which have an endothelial cell specific deletion of CaSR. The mice were then fed with a high fat diet (HFD) for 4 or 12 weeks, reflecting early and late atherosclerosis, respectively. We used histological and immuno-fluorescent stainings to analyse the atherosclerotic lesion size and its cellular and acellular composition. Systemic effects on leukocytes were evaluated using flow-cytometry, while intra-vital microscopy was used to study leukocyte adhesion to activated endothelium in-vivo. Further mechanistic studies were performed in human coronary artery endothelial cells (HCAECs) in-vitro. Results: Endothelial CaSR deficiency in mice resulted in significantly smaller lesion size in early atherosclerotic stages (4 weeks HFD), whereas late atherosclerotic lesions (12 weeks HFD) were not affected by the lack of endothelial CaSR. Moreover, the phenotype of atherosclerotic plaques, characterized by macrophage, smooth muscle cell, collagen and necrotic core content remained unaltered between wild-type and endothelial cell specific CaSR knockout mice. Interestingly, leukocyte adhesion in-vivo, especially neutrophil adhesion, was significantly reduced in endothelial cell CaSR deficient mice. In line with this, overexpression of CaSR in HCAECs in-vitro increased the production of inflammatory cytokines and expression of adhesion molecules ICAM and VCAM. Conclusion: Our results indicate that while endothelial cell specific CaSR is involved in the induction of atherosclerosis, it does not play a major role in its progression. CaSR has a major influence on endothelium-leukocyte interaction and endothelial inflammation. The increased expression of ICAM/VCAM suggest that CaSR mainly mediates such adhesive effects by modulating integrin expression. Thereby this study highlights that CaSR plays a crucial role in atherosclerosis development, rendering it a novel, so far unexplored therapeutic target.